1973
DOI: 10.1159/000149411
|View full text |Cite
|
Sign up to set email alerts
|

Common Antigens in Oncornaviruses from Continuous Human Cell Lines and Mason-Pfizer Virus

Abstract: The oncornaviruses isolated from continuous human cell lines and the Mason-Pfizer virus share a common group-specific antigen that is revealed in the immunodiffusion test. They have no common antigens with the mouse mammary tumor virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The results have been inconclusive. A number of established human cell lines were found to harbor MPMV or other type D viruses (11,18,24,25,30,36,37,46,47), but these infections were usually ascribed to laboratory contaminations (30, 47). Other investigators have described MPMVreactive antisera from normal humans (22,35,45) and those with AIDS-related or non-AIDS-related lymphadenopathy (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results have been inconclusive. A number of established human cell lines were found to harbor MPMV or other type D viruses (11,18,24,25,30,36,37,46,47), but these infections were usually ascribed to laboratory contaminations (30, 47). Other investigators have described MPMVreactive antisera from normal humans (22,35,45) and those with AIDS-related or non-AIDS-related lymphadenopathy (34).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of AIDS-related lymphoma-derived viral isolates highly similar to a prototype simian type D retrovirus raised the possibility that these viruses might be laboratory contaminants. Previous investigators have observed MPMV or MPMV-related viruses in established human cell lines (18,24,25,30,36,37,46,47). Although we identified the virus in early passages of the cultured lymphoma cells and our laboratories have never worked with monkeys, simian retroviruses, or known MPMV-infected human cell lines, the possibility of laboratory contamination could only be ruled out by direct demonstration of the virus in the patient from whom the lymphomas were obtained.…”
Section: Tatggatgac V L P Q G M a N S P T L C Q K Y V A T A I H K V Rmentioning
confidence: 99%
See 1 more Smart Citation